Antifungal activity of punicalagin isolated from Punica granatum and synergism with nystatin against Candida albicans: cellular metabolism, detection of virulence genes and proteomic analysis - Silva, Rafaela Alves da (2018)
Despite therapeutic advances, opportunistic fungal infectious diseases have increased in prevalence and have become a universal public health problem. Candida albicans (CA) is a commensal fungus that under certain environmental conditions can act as an opportunistic pathogen and colonize mucous membranes and tissues causing local and systemic infections. The emergence of drug resistant strains, as well as the increase of immunosuppressed patients, has limited therapeutic options. Therefore the aim of this study was to evaluate 1) The antifungal activity of Punicalagin (P), alone or in combination with Nystatin (N), against two CA strains. 2) The cytotoxicity effect of P and N, as well as the combination of both, on human primary cells. In the first step, yeasts of CA ATCC 90028 and SC5314 were exposed to P and N for 24 hours. The Minimal Inhibitory Concentration (MIC) of P (50 g/mL) and N (3.9 g/mL) were determined by the broth microdilution assay. The Checkerboard Assay was performed to verify the synergism between the combinations (8: PN, P8 N/4, P/8 N/2, P/8 N, P/4 N/2, P/4 N, P/2 N/4 and P/2 N/2), which were selected from the 56 combinations initially tested. The fungal metabolism was assessed by the metabolic reduction assay XTT (24h) and Minimum Microbicidal Concentration (MMC) was determined by Colony-forming unit (CFU/mL, 24h). The evaluation of virulence factors gene expression was amplified and quantified by PCR real time (Polymerase Chain Reaction-RT-qPCR, only for P/8 N/4 in 24h). The analysis of proteins related to essential biological processes of the fungus was performed by LC-MS/MS (24h). MIC and MMC of P were significantly reduced in the presence of N, indicating synergism between both. Once the antifungal potential of P was verified, we proposed to evaluate whether this drug acts through the same mechanism of action of N, altering the permeability of the cell membrane of the fungus (binding ergosterol). The evaluation of gene expression has demonstrated upregulation of some genes that may be related to a defense mechanism associated with stress or cell death. The proteomics analysis revealed alterations in the expression of several proteins in the fungi exposed to P/8 N/4 in relation to negative control, correlated with important biological processes, such as, energy metabolism, stress response, drug metabolism, among others. In the second step, cytotoxicity assays involving P and N, as well as the combination of both, were undertaken on human palate epithelial cells (HPEC) and human gingival fibroblasts cells (HGF) by Alamarblue dye. Similarly, P cytotoxicity was reduced when used in combination with N. Based on these in vitro results, the synergistic antifungal activity produced between P and N suggested that the combination of drugs, at the concentrations tested, may be a topical therapeutic or preventive alternative to be used in cases of superficial candidiasis, such as denture stomatitis.